The Influence of Land Degradation Processes and the Evolution of the Soil Profile in the Area of Izvorul Muntelui Lake (London Journal of Research In Science: Natural and Formal, 2024)
Irrational, intensive grazing and overgrazing have determined the degradation of the soil through erosion and compaction, but also the quality decrease of the pastures. The construction of roads and especially forest, county and local roads has led to slope cuts and deforestation, influencing the dynamics of the slope through the occurrence of landslides, runoff and torrentiality, as well as changes in the river bed manifested by the reduction of linear erosion, the intensification of transport and increasing material amounts of accumulation (Demeter, 2006).The modification of the landscape and by the degradation of the slopes is also influenced by the appearance of paths created by humans or animals, of cart roads causing or favouring the phenomena of trickling, torrentiality or muddy flows (Buloiu, Ionescu, 1986).Important changes were also brought by the construction of the DN15 national road, both on the relief and on the vegetation and soils. Massive clearings of beech forests mixed with conifers were made and excavations were made in slopes, embankments, embankments and excavations. The use of the land in the area of the Izvorul Muntelui Lake is dominated by forestry activities due to the large share of over 80% of the total surface, either coniferous, deciduous or mixed forests. Along the Bistricioara River valley and the immediate vicinity of the lake, there are larger areas occupied by pastures and complex crops and agricultural land mixed with natural vegetation.
Keywords: contaminants; ecosystems; Snow Pollution; Ecological Impacts; Environmental Policies.; soil degradation; landslides; land use; soil profile evolution.